Carbon dots: synthesis methods, properties and chemical sensing applications - Dang Dinh Khoi (Journal of Technical Education Science, 2020)
Carbon dots (CDs) are a novel class of fluorescent nanoparticles and carbon nanomaterials with outstanding physical, chemical properties and biocompatibility, which have attracted worldwide attention and have been applied to every branch of applied sciences from the beginning of this millennium. In this article, we have reviewed the recent progress made in this newest member of carbon nanomaterials, focusing on their synthetic strategies namely top-down and bottom-up methods. In addition, their properties including morphology and structure, compositions, optical properties (absorbance, photoluminescence properties, quantum yields and luminescence mechanisms) have been presented. For the applications of this newest member of fluorescent nanoparticles, CDs both with and without being functionalized recognition elements are selective and sensitive for sensing of analytes, including metal ions (e.g., Hg2+, Cu2+, Pb2+), non-metallic ions (e.g. sulfide ions, pyro phosphate ions, sulphite) and small organic molecules (e.g., bisphenol A, dihydroxy benzene, hydroquinone) have been reviewed. Also, the proposed fluorescence sensing mechanism of CDs have been outlined for the explanation of effectively selective and sensitive detections of inorganic ions and small organic molecules of CDs.